A decentralized beam selection for mmWave beamspace multi-user MIMO system - Pal R.; Sarawadekar K.P.; Srinivas K.V. (My University, 2025)
A millimeter beamspace multi-user multi-input-multi-output system is a key enabling technology of 5G to fulfil the demand for high data rate. But, it suffers from high RF complexity. However, RF Complexity can be reduced by the beam selection algorithm. Hence, few beam selection algorithms were proposed with a centralized approach. In this paper, a decentralized beam selection algorithm for millimeter wave beamspace multi-user MIMO is discussed. Unlike the centralized beam selection algorithm, the decentralized beam selection algorithm doesn't require a central unit or access point to select beams. The users themselves play an active role to select beams by sharing the local information with the neighbour users. This is also the requirement of a dynamic network. The performance thoroughly confides on the network cooperation to select beams in an efficient manner. The proposed decentralized beam selection algorithm enables the access point to be free from handling of a large channel matrix. Therefore, this low complexity beam selection algorithm is a better alternative. The performance and complexity of the proposed beam selection algorithm are examined in the following section. © 2019 Elsevier GmbH